Neurofilament light protein in blood as a potential biomarker of neurodegeneration in Huntington's disease: a retrospective cohort analysis. Issue 8 (August 2017) - Byrne, Lauren M; Rodrigues, Filipe B; Blennow, Kaj; Durr, Alexandra; Leavitt, Blair R; Roos, Raymund A C; Scahill, Rachael I; Tabrizi, Sarah J; Zetterberg, Henrik; Langbehn, Douglas; Wild, Edward J
Summary: Background: Blood biomarkers of neuronal damage could facilitate clinical management of and therapeutic development for Huntington's disease. We investigated whether neurofilament light protein NfL (also known as NF-L) in blood is a potential prognostic marker of neurodegeneration in patients with Huntington's disease. Methods: We did a retrospective analysis of healthy controls and carriers of CAG expansion mutations in HTT participating in the 3-year international TRACK-HD study. We studied associations between NfL concentrations in plasma and clinical and MRI neuroimaging findings, namely cognitive function, motor function, and brain volume (global and regional). We used random effects models to analyse cross-sectional associations at each study visit and to assess changes from baseline, with and without adjustment for age and CAG repeat count. In an independent London-based cohort of 37 participants (23 HTT mutation carriers and 14 controls), we further assessed whether concentrations of NfL in plasma correlated with those in CSF. Findings: Baseline and follow-up plasma samples were available from 97 controls and 201 individuals carrying HTT mutations. Mean concentrations of NfL in plasma at baseline were significantly higher in HTT mutation carriers than in controls (3·63 [SD 0·54] log pg/mL vs 2·68 [0·52] log pg/mL, p<0·0001) and the difference increased from one disease stage to the next. At any given timepoint, NfL concentrations in plasma correlated with clinical and MRI findings. In longitudinal analyses, baseline NfL concentration in plasma also correlated significantly with subsequent decline in cognition (symbol-digit modality test r =–0·374, p<0·0001; Stroop word reading r =–0·248, p=0·0033), total functional capacity ( r =–0·289, p=0·0264), and brain atrophy (caudate r =0·178, p=0·0087; whole-brain r =0·602, p<0·0001; grey matter r =0·518, p<0·0001; white matter r =0·588, p<0·0001; and ventricular expansion r =–0·589, p<0·0001). All changes except Stroop word reading and total functional capacity remained significant after adjustment for age and CAG repeat count. In 104 individuals with premanifest Huntington's disease, NfL concentration in plasma at baseline was associated with subsequent clinical onset during the 3-year follow-up period (hazard ratio 3·29 per log pg/mL, 95% CI 1·48–7·34, p=0·0036). Concentrations of NfL in CSF and plasma were correlated in mutation carriers ( r =0·868, p<0·0001). Interpretation: NfL in plasma shows promise as a potential prognostic blood biomarker of disease onset and progression in Huntington's disease. Funding: Medical Research Council, GlaxoSmithKline, CHDI Foundation, Swedish Research Council, European Research Council, Wallenberg Foundation, and Wolfson Foundation.